The Difference Of Visual Acuity And Macular Thickness Post Bevacizumab Therapy In Secondary Macular Edema Retinal Vein Occlusion - Citra Rahmadani; Nur Khoma Fatmawati; Rahmat Bakhtiar (Faculty of Medicine, University of Jember, 2018)
Retinal vein occlusion is the second most common cause of blindness in retinal vascular disease after diabetic retinopathy and may lead to complications of macular edema. Bevacizumab is an influential treatment as an anti vascular endothelial growth factor (VEGF). This study aims to determine the difference of visual acuity and macular thickness before and after treatment of Bevacizumab. This is a quasi experimental study in patients with secondary macular edema retinal vein occlusion who meets the inclusion criteria. Visual acuity and macular thickness were evaluated after one month of treatment. This study was conducted for two months since May-June 2017 by collecting secondary data from medical record at SMEC Samarinda from January 2016 – June 2017. Data were analyzed using Wilcoxon. Sixteen eyes from 16 patients were diagnosed with macular edema secondary retinal vein occlusion given bevacizumab treatment. The mean visual acuity before therapy was 1.106 LogMAR ± 0.509 and increased to 0.889 logMAR ± 0.608 (p = 0.116) after treatment while the mean macular thickness before therapy was 504.06 μm ± 301.273 and decreased to 348.81 μm ± 181.17 (p = 0.017) after treatment. There was a significant effect on the decrease in macular thickness but no significant effect on visual acuity improvement in patients with macular edema secondary retinal vein occlusion at SMEC Samarinda. Keywords: Retinal vein occlusion, macular edema, bevacizumab